Combinatorial algorithms : 26th International Workshop, IWOCA 2015 Verona, Italy, October 5-7, 2015 : revised selected papers /: 26th International Workshop, IWOCA 2015 Verona, Italy, October 5-7, 2015 : revised selected papers. (2016) - Unknown
No abstract available